ANALISIS SISTEM ANTRIAN PADA PELAYANAN JASA PT ASABRI (PERSERO) GUNA MENINGKATKAN KUALITAS PELAYANAN - Ananda Dwita Ramadhani; Hesti Wahyuni; Kurnia Ekasari; Fathimatus Zahro Fazda Oktavia (Politeknik Negeri Malang, 2022)
This research aims to find out the effectiveness of time service and the calculation of fee in the queuing system at the service counter of PT ASABRI (Persero) Branch Malang. The research was conducted by testing the steady- state, and testing the distribution using Kolmogorov Smirnov. The results showed that the steady-state value was 0.461 and has a multi channel-single phase, queuing structure with a queuing model (G/G/2): (FIFO/∞/∞). The average number of customers in the system (Ls) was 1, the average time spent by each customer at the service counter (Ws) was 8.76 minutes, the average number of customers waiting in the queue (Lq) was 0.059, the average time spent by customers waiting in the queue (Wq) was 1.86 minutes. Therefore, the hourly queue fee is IDR 49,984.067 per hour, and the monthly fee incurred is IDR 4,278.175 monthly. It can be concluded that the service counter at PT ASABRI (Persero) Branch Malang is optimal.